MAKING APPLICATIONS FOR ARCHIVING INCOMING AND OUTGOING LETTERS AT PT FELIXINDO JAYA PERKASA BASE ON VBA EXCEL - Rizki Mario Armando Saragih; Mohammad Rizal Gaffar (Records Management System Journal, 2023)
Information regarding incoming and outgoing mail is very important for companies to make decisions on the work being carried out, mistakes often occur when searching for archival data because the filing system is not detailed and irregular, therefore changes need to be made to the filing system so that it can manage data and information according to company needs. PT Felixindo Jaya Perkasa has an electronic filing system in the form of a sheet in Microsoft Excel, but the electronic archive does not include complete information so that the process of searching for archival data is not effective and efficient. Changes to the filing system are made with consideration of the effectiveness and efficiency of using the system, Visual Basic Application/VBA in Microsoft Excel can be used as a basis for making new filing system applications. VBA works with the Microsoft Excel program language which is then compiled into a company filing system application, the application is used to input incoming and outgoing mail data, and search for and delete data on company system applications so that the use of the filing system can be more effective and efficient.